Shared host genetic landscape of respiratory viral infection - Leah B. Soriaga; Dale R. Balce; Istvan Bartha; Arnold Park; Emily Wong; Michael McAllaster; Elizabeth A. Mueller; Ona Barauskas; Esteban Carabajal; Beatriz Kowalski; Sooyoung Lee; Gary Lo; et al. (Proceedings of the National Academy of Sciences, 2025)
Respiratory viruses represent a major global health burden. Although these viruses have different life cycles, they may depend on common host genetic factors, which could be targeted by broad-spectrum host-directed therapies. We used genome-wide CRISPR screens and advanced data analytics to map a network of host genes that support infection by nine human respiratory viruses [influenza A virus, parainfluenza virus, human rhinovirus, respiratory syncytial virus, human coronavirus (HCoV)-229E, HCoV-NL63, HCoV-OC43, Middle East respiratory syndrome–related coronavirus, and severe acute respiratory syndrome–related coronavirus 2]. We explored shared pathways using knowledge graphs to inform on pharmacological targets. We selected and validated STT3A/B proteins of the N-oligosaccharyltransferase complex as host targets of broad-spectrum antiviral small molecules. Our work highlights the commonalities of viral host genetic dependencies and the feasibility of using this information to develop broad-spectrum antiviral agents.